Prevalence of Tuberculosis in Severe Acute Malnutrition: A Prospective Observational Study - Thakur, Jitendra; Thakur, Ranjana; Bhatta, Nisha Keshary; Yadav, Shankar Prasad; Khanal, Basudha; Bhattarai, Narayan Raj (Journal of Nepal Paediatric Society, 2022)
Introduction: Tuberculosis (TB) and malnutrition are important causes of morbidity and mortality in children in the developing world. This study was done to determine the prevalence of tuberculosis in severe acute malnutrition (SAM) cases and to observe different presentations of SAM. Method: This prospective observational study was carried out in the Department of Paediatrics and Adolescent Medicine at a tertiary care center in Nepal for a duration of one year from December 2018 to November 2019. All cases of SAM meeting the inclusion criteria were evaluated with Mantoux test, chest X-ray, gastric aspirate / sputum analysis and gene-Xpert for diagnosis of TB. Other relevant investigations for diagnosis of TB were also sent as per the clinical scenario. Data were entered and analyzed using Microsoft excel. Descriptive statistics was used for analysis of data. Results: Total 107 SAM cases were analyzed. The hospital prevalence of wasting and severe wasting was 11.98% and 0.73% respectively. The prevalence of TB in SAM was 4.67%, commonest being pulmonary TB (60%). Among TB cases, 40% were without any systemic complaints. Only 19.6% cases presented with nutritional complaint. Conclusions: This study found that a significant percentage of cases with SAM had TB and hence adds on the importance of screening for TB (Pulmonary TB) in every case of SAM, irrespective of symptoms.